Effectiveness of Using Linanty Smart Dent Alarm As A Reminder to Brush Teeth for Primary School Age Children In Medan City - Ramadhan, Ety Sofia; Hamsar, Adriana; Herlinawati, Herlinawati; Wahyuningtyas, Miranda Gita (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2024)
According to the data on the number of dental caries in elementary school students in Medan City is quite high, with an average value of caries of 6, meaning that there are 6 caries teeth in each child's oral cavity, One of the efforts made to remind and attract the attention of children to routinely brush their teeth properly and correctly is to make a media, introduce and use a reminder alarm to brush children's teeth that is packaged as attractive as possible,Â Embedded brushing song also as an alarm tone. This study aims to determine the effectiveness of using Linanty Smart Dent Alarm as a reminder to brush the teeth of elementary school-age children in the city of Medan. The first year of research (in 2023) carried out the creation of Linanty Smart Dent Alarm, to produce Alarm media embedded with brushing songs, the distal alarm sounds at the time of 2 minimum brushing times, namely, after breakfast and before going to bed at night. In obtaining the results of Linanty Smart Dent Alarm, trials were carried out by experts, namely by media experts, psychologists and education experts. In obtaining the results of Linanty Smart Dent Alarm, trials were carried out by experts, namely by media experts, psychologists and education experts and tested for feasibility by elementary school students. Due diligence results of 86.7% stated that Linanty Smart Dent Alarm is useful and very feasible to use.